Developing a strategy map for environmental consulting firms. Issue 5 (11th June 2018) - Sayed, Naqi; Lento, Camillo
Abstract : Purpose: The purpose of this paper is to identify key performance indicators (KPIs) for environmental consulting firms, explore their causal linkages and develop a strategy map around the balanced scorecard (BSC) perspectives. Design/methodology/approach: Relevant KPIs are identified through interviews and secondary data. Causal relationships between KPIs are explored by using the decision-making trial and evaluation laboratory (DEMATEL) method to analyze survey responses from senior partners and industry experts. Findings: The results suggest that the learning and growth perspective plays a pivotal role for consulting firms. In addition, and contrary to views held by some, internal process perspective can play a significant cause factor role for service businesses. Among the KPIs which were identified as important, acquiring new skills/techniques, increased customer value proposition, personnel utilization, new product solutions and start to end solutions as KPIs exhibited both cause and effect characteristics. Practical implications: The results isolate core KPIs which self-reinforce, complement each other and form a feedback loop. Active management and monitoring of these KPIs is likely to result aid a consulting firm in achieving strategic objectives. The strategy map developed in this study can also serve as a reference point for similar businesses. Originality/value: This is the first known study to develop a strategy map for a consulting business by adopting a structured approach and identify causal link among BSC perspectives and their respective KPIs. The study provides further empirical evidence for usefulness of a structured approach such as the DEMATEL.